Book Review of Mariana Mazzucato's (2014). The entrepreneurial state: debunking the myth of the public sector vs. the private sector - Bagattolli, Carolina; Naves de Deus Dornelas, Larissa; Krajevski, Luis Claudio; Rocha de Pauli, Dayane; Pereira, Wellington; Lobato Torres, Ricardo (NOvation — Critical Studies of Innovation, 2024)
The Italian economist Mariana Mazzucato aims to dispel the commonly associated image of the state in theoretical and political discourse, which tends to portray it as a bureaucratic, inefficient entity, expensive for society. Her book is a necessary contribution to the debate on the role of the state and the limitations of the market as an agent capable of solving socioeconomic problems and challenges on its own. The last four decades have marked the rise of neoliberalism as the obligatory economic framework worldwide, leading to an increasing questioning of the state’s role in the economy and perception of it as unnecessary. Mazzucato’s meticulous argumentation contributes to retrieving evidence to clarify this debate and to understand the fundamental role that the state and public funding have been playing in the innovation process of major corporations.